Investigation into the Realization of Naturalism in Hashtgerd New Town Based on the Iranian Islamic Model - Meshkini, Abolfazl; Ghasemi, Akram; Hamzehnejad, Mahdi; Oskui, Azita Belali (International Journal of Geography and Geology, 2013)
Naturalism has been regarded as one of the most significant indices of the appraisal of the identity of Iranian Islamic cities. This index, by the emergence of the new era, in spite of the lucidity in the urban structures, is not deemed as an identity determiner owing to its combination with other elements, and consequently taking new roles and functions. This study focused on naturalism manifested in the presence of natural elements such as water, fountains, ponds, pools, water running in water paths on either side of roadways and streets, green spaces, the sun shining, and the wind flowing. In order to evaluate the index of naturalism in the design of Hashtgerd New Town, 379 inhabitants of this city participated in the present study. This is an applied research and a descriptive-analytical approach was utilized. For data collection, methods of library and field research were adopted. For data analysis, Frequency, Mean, and Standard Deviation were estimated and a One-sample T-test was conducted via SPSS software. The results revealed that the index of naturalism in line with the unique criteria of Iranian Islamic urban construction has been overlooked by the urban designers and constructors of Hashtgerd New Town.